Effect of Annealing Temperature of Ni-P/Si on its Lithiation and Delithiation Properties. Issue 4 (17th February 2020) - Domi, Yasuhiro; Usui, Hiroyuki; Ueno, Ayumu; Shindo, Yoshiko; Mizuguchi, Hayato; Komura, Takuro; Nokami, Toshiki; Itoh, Toshiyuki; Sakaguchi, Hiroki
Abstract : Annealed Ni–P–coated Si (Ni–P/Si) anodes for lithium-ion batteries have shown a superior cycle life with discharge capacity of 1000 mA h g −1 over 1100 cycles in some ionic-liquid electrolytes. However, the annealing temperature has yet to be optimized for Ni–P/Si electrodes. We investigated the electrochemical performance of Ni–P/Si electrode annealed at various temperatures in this study. The Ni–P/Si electrodes annealed at 800 ± 20 °C exhibited a superior cycle life with a reversible capacity of 1000 mA h g −1 over 1000 cycles, whereas the capacity of the electrodes annealed at temperatures of 750 °C and 850 °C faded at approximately 500 cycles. At 800 °C, a newly formed NiSi2 phase was theorized to significantly contribute to improving adhesion between the Ni–P coating layer and the Si particles. The Ni–P coating particles tended to aggregate at 850 °C, leading to a reduction in the coating effect, that is, a decline in their reactivity with Li +, acceleration of electrode disintegration, and a reduction in electrical conductivity. On the other hand, Ni–P/Si electrodes annealed at 850 °C exhibited a superior rate performance. The amount of available NiSi2 which ultimately contributed to higher reactivity with Li should increase.